PdBr2‐Catalyzed Acetal Formation of Carbonyl Compounds Using Diazophenanthrenequinone: Utility of 9, 10‐Phenanthrenedioxyacetal. Issue 33 (5th June 2020) - Kitamura, Mitsuru; Fujimura, Ryo; Nishimura, Tomoaki; Takahashi, Shuhei; Shimooka, Hirokazu; Okauchi, Tatsuo
Abstract : We developed a new acetalization method of ketones and aldehydes under non‐acidic conditions using diazophenanthrenequinone and PdBr2 . The formed acetals that have a phenanthrene skeleton withstand under mild acidic conditions. Removal of acetals was successfully proceeded under strong acidic or oxidation conditions using aqueous ceric ammonium nitrate (CAN) to afford corresponding ketones and aldehydes. Abstract : A new acetalization method of ketones and aldehydes under non‐acidic conditions was developed using diazophenanthrenequinone and PdBr2 . The formed acetals that have a phenanthrene skeleton withstand under mild acidic conditions. Removal of acetals was successfully proceeded under strong acidic or oxidation conditions using aqueous ceric ammonium nitrate (CAN).